JAŃA REDAKCIYADAǴÍ ÓZBEKSTAN RESPUBLIKASÍ KONSTITUCIYASÍ HÁM ONÍŃ ÁHMIYETI - Tilewov, E. (SCIENCE and SOCIETY, 2024)
In the article, the new version of the Constitution of the Republic of Uzbekistan and its adoption on the basis of a national referendum, as well as the changes made to the constitution, were discussed in detail. The newly revised Constitution consists of 6 sections, 27 chapters, and 155 articles.